Reclaiming Possession: A Critique of the Discourse of Dispossession in Indigenous Studies - Reid, Julian; Justus Liebig University Giessen (My University, 2018)
Indigeneities are widely constructed as emanating not only from the experience of dispossession in the historical past, but as ways of being in the world which are grounded positively in dispossession, and which in being so offer themselves as antagonistic alternatives to Western ways of being, grounded aggressively as they are in possessiveness, of land, of self, and of others. This essay argues that the opposite is true; that the present condition is one of being governed by regimes of power the strategy of which depends on the production of dispossessed and non-possessive subjects. The task is to reject these discourses of entrapment and reclaim possession for ourselves. In doing so much can yet be learned from minor traditions of thought and practice among indigenous peoples, both mythic and real, which, in contrast to today s dominant discourses on indigeneity, insist on the integral importance of possession as a foundation for political subjectivity. Whether indigenous or non-indigenous, the task is the same; avoid being trapped by power, learn instead to hunt power, and cultivate the ultimate freedoms of autonomy and self-possession.
Keywords: dispossession; indigeneity; land; possession; power; subjectivity; ddc:300